The neural mechanism and pathways underlying postoperative nausea and vomiting: a comprehensive review - Zhu Zhang; Xin Wang (European Journal of Medical Research)
Abstract This scoping review aims to synthesize evidence regarding the neural mechanisms and pathways underlying postoperative nausea and vomiting (PONV). We systematically searched the PubMed, Embase and Cochrane Library databases up to 2024. The findings indicate that PONV is a common complications after surgeries involving anaesthesia and can also lead to severe postoperative discomfort. Various surgical procedures and anaesthesia methods can trigger PONV, and the underlying neural mechanisms and signalling pathways are complex. It is currently assumed that these pathways do not exist independently of each other but that a central mode generator encompasses all relevant neurons and conducting nerve fibres, including the nucleus of the solitary tract, the dorsal nucleus of the tenth nerve, the area of the nerve, etc. After the information is integrated, it is transferred to the digestive tract, thereby causing PONV. In this article, we discuss the progress of research on the factors that influence PONV and identify the underlying pathways.